Psychotropic Drug Use before, during, and after Pregnancy: A Population-Based Study in a Canadian Cohort (2001-2013). (August 2017) - Leong, Christine; Raymond, Colette; Château, Dan; Dahl, Matthew; Alessi-Severini, Silvia; Falk, Jamie; Bugden, Shawn; Katz, Alan
Objective: To describe the extent of increase in use and the rate of continuation versus discontinuation of psychotropic agents before, during, and after pregnancy. Methods: Rates of psychotropic use (antidepressants, anxiolytic/sedative-hypnotics, antiepileptics, antipsychotics, lithium, stimulants) among women with a hospital-recorded pregnancy outcome were assessed using databases at the Manitoba Centre for Health Policy. Rate of use was defined as ≥1 prescription over the total number of pregnancies in the 3-12 months before pregnancy, 0-3 months before pregnancy, during pregnancy, or 3 months after pregnancy. Continued use was defined as ≥2 prescriptions with gap ≤14 days. Poisson regression was used to analyze trends. Results: Over the study period, a psychotropic drug was used before, during, or after pregnancy in 41, 923 of 224, 762 pregnancies. From 2001 to 2013, psychotropic use increased 1.5-fold from 11.1% to 16.2% ( p < 0.0001) in the 3-12 months before pregnancy, 1.6-fold from 6.4% to 10.5% ( p < 0.0001) in the 3 months before pregnancy, 1.8-fold from 3.3% to 6.0% ( p < 0.0001) during pregnancy, and 1.5-fold from 6.2% to 9.5% ( p < 0.0001) in the 3 months postpartum. Among the 13, 579 women who received at least 1 psychotropic agent in the 3 months prior to pregnancy, 38.5% stopped the agent prior to pregnancy and only 10.3% continued use throughout pregnancy. Continued use throughout pregnancy was higher (56.9%) among the 6693 women who received at least 2 prescriptions for a psychotropic agent and were at least 80% adherent in the 3 months prior to pregnancy. Conclusion: The use of psychotropic agents increased over 12 years. The safety of continuing versus discontinuing these agents during pregnancy remains uncertain, but we observed a decrease in psychotropic drug use during the pregnancy period.